Malayan Tapir Behaviour, Habitat Use And Density In Belum, Perak. - Christopher, Wong Chai Thiam (2021)
Listed as endangered under the IUCN Red List of Threatened Species, the ecological knowledge for the Malayan tapir is still severely lacking; not only for Peninsular Malaysia, but also for the Southeast Asia region. Estimated to be between 1,500 to 1,700 individuals left in the country, the Malayan tapir is now threatened mainly by habitat loss, and fragmentation. In recent years, there has been an increase in tapir road-kills due to the direct impact of road fragmentation. Large-scale natural forest conversion has likely caused tapirs to venture out into human dominated areas. In an effort to conserve Malayan tapirs, this thesis therefore seeks to better understand the population ecology of tapir by investigating its activity pattern, factors that influence its habitat preference, assessing its population status and Relative Abundance Index (RAI) within RBSP, a primary forest and TFR, a selectively logged forest. The Malayan tapir’s activity pattern was found to be predominantly nocturnal; 1900 hrs to 0659 hrs (83.20%). Activity pattern of the Malayan tapir is not significantly different with predominantly diurnal activity of human in the landscape (P>0.05, Mann-Whitney) with kernel density estimate of 0.16 (CI: 0.10-0.22) in TFR and 0.12 (CI: 0.07-0.17) in RBSP. Spatial avoidance towards human habitation was observed from the habitat use analysis, where the Malayan tapir was found to prefer forested areas which are away from the human settlements and at high elevation in the RBSP and TFR landscape.